Assessment of Underground Water Quality in Karimunjawa Island, Central Java – Indonesia - Joko Prihantono; Yulius Yulius; Semeidi Husrin; Muhammad Ramdhan; Wisnu A. Gemilang (Jurnal Segara, 2021)
As a small island and tourist destination, Karimunjawa municipal is need fresh water to support the tourist activity, mainly to supply drinking water. Unfortunately, freshwater on a small island is obtained from groundwater which is very limited and vulnerable to climate change and anthropogenic activities. A groundwater assessment is necessary to receive up-to-date information on groundwater quality, to assess the groundwater feasibility for drinking water, and determine the pollutant source. The assessment was conducted by collected groundwater sampling from dug wells and swamp area in Karimunjawa municipal and then analyzed the samples in the laboratory to obtain the value of Nutrient (NO3-, NO2-, NH3-N); Heavy Metals (Cu, Fe, and Pb); and Salt (TDS, Cl-, Na+). These obtained parameters were compared with the quality standard of the minister of health regulation of the Republic of Indonesia about water quality standards for drinking water. In this study, 14 samples were collected and analyzed. The result shows that nutrient contaminant is low, but some groundwater sample was contaminated by ammonia. Heavy metal is undetectable, but almost all samples are contaminated by salt. Therefore, the groundwater in Karimunjawa municipal experienced seawater intrusion and not feasible to be consumed as drinking water.